Proteolytic and mechanical remodeling of the extracellular matrix by invadopodia in cancer. (1st January 2023) - Perrin, L; Gligorijevic, B
Abstract: Cancer invasion and metastasis require remodeling of the adjacent extracellular matrix (ECM). In this mini review, we will cover the mechanisms of proteolytic degradation and the mechanical remodeling of the ECM by cancer cells, with a focus on invadopodia. Invadopodia are membrane protrusions unique to cancer cells, characterized by an actin core and by the focal degradation of ECM via matrix metalloproteases (MMPs). While ECM can also be remodeled, at lower levels, by focal adhesions, or internal collagen digestion, invadopodia are now recognized as the major mechanism for MMP-dependent pericellular ECM degradation by cancer cells. Recent evidence suggests that the completion of epithelial-mesenchymal transition may be dispensable for invadopodia and metastasis, and that invadopodia are required not only for mesenchymal, single cell invasion, but also for collective invasion. During collective invasion, invadopodia was then shown to be located in leader cells, allowing follower cells to move via cooperation. Collectively, this suggests that invadopodia function may be a requirement not only for later steps of metastasis, but also for early invasion of epithelial cells into the stromal tissue. Over the last decade, invadopodia studies have transitioned into in 3D and in vivo settings, leading to the confirmation of their essential role in metastasis in preclinical animal models. In summary, invadopodia may hold a great potential for individual risk assessment as a prognostic marker for metastasis, as well as a therapeutic target.